SAT0040 Assessing 5-year radiographic progression in rheumatoid arthritis patients with moderate disease: findings from a uk multi-centre prospective observational study. (15th June 2017) - Carpenter, L; Norton, S; Nikiphorou, E; Jayakumar, K; McWilliams, DF; Dixey, J; Kiely, P; Walsh, DA; Young, A; ,
Abstract : Background: Early, intensive treatment to achieve remission, or at least low disease target (Treat-to-Target, T2T), is advocated to prevent and/or reduce structural joint damage and disability in early Rheumatoid Arthritis (RA). A recent study shows how patients with moderate disease exhibit similar rates of functional disability and orthopaedic surgical interventions to those patients with high disease 1 . To our knowledge, no study has looked at longitudinal observational data to investigate the progression of structural joint damage in these patient sub-groups. Objectives: To investigate the long-term progression of radiographic joint damage in patients with sustained moderate disease activity. Methods: Demographic, clinical, laboratory and radiographic data from the Early Rheumatoid Arthritis Study (ERAS) was available for 1, 465 patients. Radiographic damage was scored using the modified Sharp/van der Heijde (SvdH) method. The original three variable 44 joint count Disease Activity Score (DAS-44) was used. Mean DAS-44 over the first 5 years was estimated for patients with at least two DAS-44 scores. Patients were stratified based on EULARs thresholds of low (<2.4), moderate (2.4–3.7) and high (>3.7) disease. Mixed-effects negative binomial regression modelled patients' radiographic progression over 5 years, whilst controlling for key confounders, including age at onset, sex, rheumatoid factor status and baseline functional disability. Results: A total of 1, 110 patients with 3, 751 observations over the 5 year period (mean =3.4 observations per patient) were analysed. 396 (36%), 363 (33%) and 351 (32%) patients were classified in the low, moderate and high DAS-44 groups respectively. The low group had lower SvdH scores at 1 year compared to the moderate group (12.9 vs. 19.2, p<0.001). Furthermore, the low group also experienced half the annual rate of change over the 5 years compared to the moderate group (3.6 vs. 7.4, p=0.002). In contrast, the high group had similar SvdH scores at year 1 compared the moderate group (20.4 vs. 19.2, p=0.884), but increased annual progression over the 5 years (10.0 vs. 7.4, p=0.010). Despite the increased annual progression rate, the difference in SvdH scores between the moderate and high groups remained non-significant at 5 years. Conclusions: Sustained moderate disease over the first five years of RA indicates similar levels of radiographic progression compared to sustained high disease. This study provides support on the importance of tight treatment control with early and aggressive therapy according to T2T principles. Preventing sustained moderate disease activity states can help reduce radiographic progression and consequently joint destruction, minimising the risk of disability in the long-term. References: Nikiphorou, E. et al. Association between rheumatoid arthritis disease activity, progression of functional limitation and long-term risk of orthopaedic surgery: combined analysis of two prospective cohorts supports EULAR treat to target DAS thresholds. Ann. Rheum. Dis. annrheumdis–2015–208669 (2016). Disclosure of Interest: L. Carpenter Grant/research support from: NIHR Programme Grant, S. Norton: None declared, E. Nikiphorou: None declared, K. Jayakumar: None declared, D. McWilliams: None declared, J. Dixey: None declared, P. Kiely: None declared, D. Walsh: None declared, A. Young: None declared